2020
DOI: 10.3390/jof6040347
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Vaccination with Cationic Liposomes Formulated with Dioctadecyldimethylammonium and Trehalose Dibehenate (CAF01) and Peptide P10 Is Protective in Mice Infected with Paracoccidioides brasiliensis

Abstract: The peptide P10 is a vaccine candidate for Paracoccidioidomycosis, a systemic mycosis caused by fungal species of the genus Paracoccidioides spp. We have previously shown that peptide P10 vaccination, in the presence of several different adjuvants, induced a protective cellular immune response mediated by CD4+ Th1 lymphocytes that was associated with the increased production of IFN-γ in mice challenged with a virulent isolate of Paracoccidoides brasiliensis. Cationic liposomes formulated with dioctadecyldimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…There is a consensus that the therapeutic vaccine instead of the prophylactic one would be the best way to control PCM. Several works have demonstrated that a therapeutic vaccine to boost the cellular immune response seems relevant not only to reduce the time of treatment but also to prevent relapses and improve the prognosis of anergic cases [30][31][32]. P10 has previously been well characterized as an epitope for CD4 + T cells [16], and many studies have shown the ability of this peptide to generate a protective immune response against P. brasiliensis in different preparations (Freund's complete adjuvant, Salmonella enterica flagellin FliC) [16,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a consensus that the therapeutic vaccine instead of the prophylactic one would be the best way to control PCM. Several works have demonstrated that a therapeutic vaccine to boost the cellular immune response seems relevant not only to reduce the time of treatment but also to prevent relapses and improve the prognosis of anergic cases [30][31][32]. P10 has previously been well characterized as an epitope for CD4 + T cells [16], and many studies have shown the ability of this peptide to generate a protective immune response against P. brasiliensis in different preparations (Freund's complete adjuvant, Salmonella enterica flagellin FliC) [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of P10 either before or after the establishment of PCM produces a therapeutically protective effect in both immunosuppressed and immunocompetent mice [32]. P10 requires concomitant administration of adjuvant for efficacy, although diverse adjuvants produce a therapeutic effect with the peptide [31], including delivery as a P10-nanoparticle [30].…”
Section: Discussionmentioning
confidence: 99%
“…Paracoccidioidomycosis is endemic among rural populations, affecting males in the productive age group (30-60 years) and is related to agricultural activities. The etiologic agent is a thermodimorphic fungus (Paracoccidioides brasiliensis) (Araújo et al, 2020;Turissini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%